Spatiotemporal Analysis of Lumpy Skin Disease in Türkiye (2013-2021) - Bayir, Tuba (Sciendo, 2024)
Lumpy skin disease (LSD) is a serious, transboundary disease that affects cattle all over the world and results in considerable productivity losses. Although T & uuml;rkiye's first outbreak of LSD was reported in August 2013, there is very little information available about the outbreak's spatiotemporal distribution or severity. GIS-based data analysis provides crucial tools for describing the spatial epidemiology of the disease by assessing the spatial distribution of LSD across time. This study used information on outbreaks reported to the the World Animal Health Organization (WOAH-OIE) between 2013 and 2021 to conduct a retrospective study on the epidemiology of LSD in T & uuml;rkiye. Differences in the number of reported outbreaks and cases across different regions, provinces, months, and years were evaluated and descriptive statistics were calculated. In addition, spatial statistical tests (Local Moran's I and Getis-Ord Gi*) and Geographical Information Systems (GIS) were used to assess LSD outbreaks that had taken place at the province level in T & uuml;rkiye. Possible epidemiological clusters of LSD were identified. A total of 1787 outbreaks and 10109 cases of LSD were reported from 75 out of 81 provinces of T & uuml;rkiye during the course of the nine-year period. Hotspots for the circulation of LSD were identified in the Aegean, Southeastern and Eastern regions using spatial cluster analyses and it was observed that the spatial autocorrelation of LSD cases is positive across the country. The findings from this study, it may help us comprehend the disease's spatial character and offer authorities the beneficial information for surveillance efforts.
PROSTORNO VREMENSKA ANALIZA BOLESTI KVRGAVE KO?E U TURSKOJ (2013-2021)
Keywords: Cluster analysis; Epidemiology; Lumpy skin disease; Outbreak; Spatial analysis; T & uuml;rkiye